A Decoupling Technique for Beamforming Antenna Arrays Using Simple Guard Trace Structures - Zulfi Zulfi; Joko Suryana; Achmad Munir (DRPM - ITB, 2023)
This paper discusses decoupling techniques for suppressing electromagnetic coupling between elements of beamforming antenna arrays. Guard trace structures, which are commonly used for crosstalk reduction on printed circuit board technology, are proposed to be inserted between the array elements for coupling reduction. Two types of guard trace structures, i.e., straight guard traces and serpentine guard traces, were explored, and the effect of using via holes on both types of guard traces was studied. For this purpose, two-element antenna arrays with guard trace structures inserted between array elements were designed and simulated. The simulation results showed that a straight guard trace with vias (straight GTV) and a serpentine guard trace without vias (serpentine GT) could effectively reduce EM coupling between elements of array antennas. To verify the simulation results, prototypes of antenna arrays with straight GTV and serpentine GT were realized and measured. The measurement results showed coupling reductions of 5 dB and 6.4 dB could be achieved when straight GTV and serpentine GT are inserted between two array elements separated by edge-to-edge distances of 4 mm and 9.05 mm, respectively. Therefore, the proposed decoupling technique is suitable for beamforming antenna arrays with a very close distance between array elements.